Estimated Impacts Induced by The Magnetic Activity Index (Dst) on the Local Total Electronic Content (TEC) in Africa Equatorial Zone - Dinga, Jean Bienvenu; Okolandzaud, Oba Péa; Poaty, Jocelyn Franck-Patient Boungou; Biona, Clobite Bouka (European Journal of Applied Sciences, 2023)
The state of equatorial ionosphere has been studied from the determination of the Total Electron Content (TEC) based on the correction of errors propagation of GPS signals due to ionospheric disturbances using the dual frequency method. In our study, we considered tree stations of the equatorial area (adis, bjco and nklg) in January 2012. Firstly, the monthly survey of the TEC has revealed that the magnetic storm days coincide with the days that the TEC Rinex around 70 UCET. Secondly, the daily survey of the TEC reveals two TEC ( TEC/RINEX and the TEC/CODG) has revealed that during magnetics storms days, the interval between curves of TEC observed between 10: 00PM to 16:00PM (UT) is more important (around 10 UCET) when the Dst is strongly negative whatever the nature of the magnetic storm, and the interval between curves of TEC observed between 17:00 to 20:00PM (UT) is function of the nature of the magnetic storm.